Pengaruh Kebijakan Pengeluaran Pemerintah terhadap Kualitas Infrastruktur di Negara Berkembang - Nurul Aini Harahap; Suci Indah Triani; Ahmad Wahyudi Zein (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
Government spending policy plays a key role in providing funds for the development and maintenance of infrastructure, including transportation, energy, clean water, and other public facilities. This study aims to analyze the effect of government spending policy on the quality of infrastructure in developing countries, with a focus on the effect of government budget allocation in the infrastructure sector on improving the quality of services and its impact on the regional economy.